Harikhali in Paigachha, Bangladesh - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Photos from the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) research benchmark site in Bangladesh.